Pusat Seni Teater Di Pekanbaru Dengan Pendekatan Arsitektur Kontemporer - Rusydina Sabila Fauzi; Wahyu Hidayat; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Theater Arts Center with Contemporary Architecture Approach is a venue that serve for activities related to the theater arts, including introduction activities, learning, training, gathering places, to the final process of the show. The world of art has always evolved as a reflection at that time in line with the development of contemporary architecture that is innovative both from the shape and appearance as the use of materials that will support the look of contemporary architectural styles. This design aims to support theater arts activities and interest of the younger generation to be more creative. The methods of research that is used, field data collection, literature study and empirical studies. The concept used is freedom of expression that is sad, happy, and angry that poured into the building. The results of this study design a superior building in the field of theater with the principle of application of Contemporary Architecture in terms of varied forms, neutral building colors, flexible materials use and create something innovative on buildings in according to the times. Key word: Theater Art Centre, Architecture, Contemporary, Freedom of Expression